Drug resistance and cellular adaptation to tumor acidic pH microenvironment - Wojtkowiak, Jonathan W. (2011)
Despite advances in developing novel therapeutic strategies, a major factor underlying cancer related death remains resistance to therapy. In addition to biochemical resistance, mediated by xenobiotic transporters or binding site mutations, resistance can be physiological; emerging as a consequence of the tumor’s physical microenvironment. This review focuses on extracellular acidosis, an end result of high glycolytic flux and poor vascular perfusion. Low extracellular pH, pHe, forms a physiological drug barrier described by an “ion trapping” phenomenon. We describe how the acid-outside plasmalemmal pH gradient negatively impacts drug efficacy of weak base chemotherapies but is better suited for weakly acidic therapeutics. We will also explore the physiologic changes tumor cells undergo in response to extracellular acidosis which contribute to drug resistance including reduced apoptotic potential, genetic alterations, and elevated activity of a multidrug transporter, p-glycoprotein, pGP. Since low pHe is a hallmark of solid tumors, therapeutic strategies designed to overcome or exploit this condition can be developed.